Pengaruh Tingkat Partisipasi Terhadap Tingkat Kesejahteraan Masyarakat dalam Pengembangan Objek Wisata Curug Jagapati Kabupaten Garut - Moch. Agus Syadad Saefullah; Ridwan Iskandar; Odang Rusmana; M. Romi Okta Viano; Gilang Ramadhan (CV. Ulil Albab Corp, 2022)
Based on data, the development process in the tourism sector is carried out as an effort to provide large income for regional income and increase community welfare, besides that it is closely related to the cultural and natural attractiveness of an area. Tourism development can’t be separated from the participation of the people who live around the tourist attraction area. This research aims to find out how the level of participation of the Neglasari village community is, find out how the level of welfare of the Neglasari village community is and find out how much influence the level of participation has on the level of community welfare. A quantitative approach is used in this study. The population used in this study was 6,181 people, simple random sampling was used so that 98 respondents were obtained. The results of this study indicate that the level of community participation and the level of welfare are in the medium category. This study also shows that there is a significant influence between the level of participation on the level of community welfare is 58.3%